Quantum Leaps in School Leadership - Rettig, Perry R. (Rowman & Littlefield Publishers, 2002)
This book theorizes that models based on the classical sciences have misguided educational leadership. Dr. Rettig sees the open dynamics of twentieth-century science — specifically, quantum mechanics — as a better and more natural model, and describes what he sees as a method of leadership light years beyond those of today. Dr. Rettig illustrates his erudite critique of the contemporary school administration structure with the story of Leslie O'Connor, a fictional administrator, who makes her way through familiar-seeming training techniques. For anyone interested in the organization and administration of school systems, this book provides an original and compelling perspective.